Role of spatial analysis technology in power system industry: An overview. (December 2016) - Shafiullah, Md; Rahman, Syed Masiur; Mortoja, Md. Golam; Al-Ramadan, Baqer
Abstract: Power system networks are the largest and most complex systems ever devised by human being. The networks are associated with huge amount of investments where the success of the sector heavily depends on appropriate planning and management. Spatial analysis technologies play very important role in planning, monitoring, and managing of the network by comprehensively considering social, environmental, and economic issues. Spatial analysis, the heart of geographic information systems (GIS) provide an integrated platform for proper management and planning of power systems. The major role of GIS technology includes: (i) developing spatial model for power generating stations, transmission networks, and distribution substations; (ii) determining suitable locations for power generation and distribution stations, and optimal routing of transmission networks; and (iii) integrating renewable energy resources with the planning and management system. Parallel to GIS, global positioning systems (GPS) has introduced new dimensions in spatial research because of its increasing availability with reduced price. The integration of GPS in data measurement techniques made a paradigm shift in (i) monitoring of the power system network with time synchronized data and (ii) finding fault locations as well as taking corrective actions with better accuracy. This paper investigates the evolutionary role of GIS and GPS technologies in different components of power system networks. These technologies are expected to provide a smart and promising platform for integrating virtually all the relevant information and systems required to develop and maintain a sustainable power system networks at local, national, regional, and global levels.